Collaboration Trumps Intelligence as a Predictor of Standard of Living - Dennis Ridley (Research in Applied Economics, 2024)
Human beings are intelligent. More importantly, they are a social species capable of cooperation. Other animals in the kingdom can cooperate. But human beings further distinguish themselves by their innate ability to collaborate. They not only take care of their children they also take care of each other. The purpose of this paper is to compare the relative impacts of collaboration and intelligence on economic growth and development. We illustrate by data and analysis, that collaboration is superior to intelligence as a predictor of per capita real gross domestic product adjusted for purchasing power parity. Collaboration is found to be a statistically significant predictor and intelligence quotient (IQ) is not.